Pengendalian mutu modified cassava flour (mocaf) di PT. Rumah Mocaf Indonesia, Banjarnegara, Jawa Tengah - Afist Azkiya Sidqi; Ika Dyah Kumalasari (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Indonesia is a country with abundant products in agriculture and plantation. One of the agricultural products in Indonesia is cassava. PT Rumah Mocaf Indonesia is a company that focuses on developing mocaf products to improve the welfare of cassava farmers and drive the rural economy. Company produce mocaf following company standards and SNI, one of the requirements is quality control of mocaf production for continuous evaluation and improvement to achieve the condition with no defective products. The purpose of mocaf quality control is to find out the types of defects and the factors that cause them. The sampling method, in this case, used random sampling, and the quality control used The Seven Tools method combining Pareto Chart and Fishbone Diagram. Based on the results of the analysis that has been carried out, the results of the Pareto Chart show that there are several types of defects, there are in odor, color, and moisture, with the chief defect of mocaf found in the odor criteria of flour with 44 % chief defect. The results of the Fishbone Diagram show the factors that cause defects in mocaf are influenced by man factor due to the lack of knowledge and skills when carrying out the mocaf productions, material factor due to long growing period with high moisture content, method factor due to unstable drying temperature and enzyme dose and time during fermentation there are not following regulations, machine factor due to dirty machine and small capacities of the machine, and environment factor due to unpredictable weather and temperature.